Impact of SARS-CoV-2 Variant NSP6 on Pathogenicity: Genetic Analysis and Cell Biology - Yangye Gao; Peng Ni; Yanqiao Hua; Shuaiyin Chen; Rongguang Zhang (Current Issues in Molecular Biology)
SARS-CoV-2 nonstructural protein (NSP) 6 is one of the factors affecting viral pathogenicity. Mutations in NSP6 continuously emerge during viral transmission and are closely associated with alterations in viral pathogenicity. This study investigated the structural and functional impacts of NSP6 mutations by analyzing NSP6 proteins from the Wuhan-Hu-1/B (WT) strain and predominant variants Alpha, XBB.1.16, BA.2.86, and JN.1 using bioinformatics, transcriptomics, and cellular experiments. The results demonstrate that the V3593F mutation decreased the β-sheet proportion and modified hydrogen bonding patterns, while the L3829F mutation enhanced structural stability by promoting random coils. The R3821K substitution exposed lysine residues, potentially enhancing molecular interactions. Combined transcriptomic profiling and functional assays revealed that WT-NSP6 significantly inhibited poly (I: C)-induced immune factor transcription and reduced the phosphorylation levels of p-IRF3 and p-STAT1, effects absent in the XBB.1.16 variant. Furthermore, WT-NSP6 markedly activated p-AKT and p-mTOR expression, with JN.1-NSP6 maintaining limited capacity to upregulate p-mTOR. However, p53 inhibitor treatment reversed Alpha-NSP6- and BA.2.86-NSP6-upregulated p-mTOR protein expression in cells. This study demonstrates that a high frequency of NSP6 mutations alters NSP6’s structure, impairing the type I interferon signaling pathway and affecting host antiviral responses through the p53-AKT-mTOR signaling pathway. These findings contribute to the understanding of evolution, immune evasion, and viral pathogenesis mechanisms, with potential implications for the development of antiviral therapies and preventive strategies for this viral infection.